Análise crítica de gêneros de popularização da ciência da área de informática no jornal Zero Hora (2009) - Moreira, Tânia Maria (2012)
The present study aims at investigating, under the perspective of Critical Genre Analysis (MEURER, 2002; 2006; MOTTA-ROTH, 2005; 2006) and based on studies about science and its popularization (SOUZA SANTOS, 2006; VOGT, 2003; 2010; MOTTA-ROTH, 2009; 2010), the configuration of texts that popularize research in the area of Informatics, by trying to identify the conditions of production, distribution and consumption in Zero Hora newspaper. This study is based on the importance of analyzing discourses to qualify the language teaching. As a Portuguese language teacher, I understand that I need to position myself as a discourse analyst in order to contribute in the critical formation of Basic Education students. Critical Genre Analysis articulates three theoretical perspectives of social approaches in language studies: the socio-rhetorical theory (SWALES, 1990; 2004), Systemic-Functional Linguistics (HALLIDAY, 1978; HALLIDAY; HASAN, 1989) and Critical Discourse Analysis (FAIRCLOUGH, 1992; 1999; 2001; 2002; 2003). The research corpus is composed by 27 science popularization texts from the field of Informatics, published in the Economy section of Zero Hora newspaper in 2009. The analytical procedures adopted involved the study of the context and texts. In the contextual analysis, conducted through bibliographical studies selection, documental data available in the newspaper website and interview with the producer of the Economy section in the studied media, I try to identify and interpret the contexts of culture and situation of the newspaper. In the textual analysis, I describe and interpret how two analytical categories are configured: rhetorical organization and intertextuality. The results indicate that Zero Hora newspaper produces news, news report, and infomercial, a hybrid genre (FARICLOUGH, 2001, p. 149) which merges characteristics from the news and advertisement genres in the recontextualization of reports of research conclusions in the Field of Informatics. These discursive events are considered hybrid genres because they combine marks of journalistic, scientific and pedagogic discourses which point to an approach of commodification.